Web attacks: defeating monetisation attempts. Issue 5 (May 2019) - Nguyen, Van-Linh; Lin, Po-Ching; Hwang, Ren-Hung
Abstract : According to Internet Live Stat, the total number of online websites has already soared over 1.9 billion and is steadily increasing. 1 The most popular content management systems (CMS) installed on such websites are PHP-based frameworks such as Wordpress and Joomla, which account for (as of December 2018) 59% and 6% of market share. 2, 3 A large number of those websites belong to small companies and individuals that may have few motivations to pay thousands of dollars for security maintenance services. Also, due to development costs, the owners – even the developers they hire – may prefer an off-the-shelf CMS such as Joomla to accelerate deployment. A large proportion of the nearly two billion websites now on the Internet are run by individuals and organisations without the skills or resources to make them secure. These sites are targets for cyber criminals looking to exploit weaknesses to 'monetise' them. Van-Linh Nguyen, Po-Ching Lin and Ren-Hung Hwang of the National Chung Cheng University, Taiwan, examine the tactics employed by criminals and present a framework for preventing such attacks, while acknowledging that this is a battle that is likely to continue.